Co-administration of treatment for rifampicin-resistant TB and chronic HCV infection: A TBnet and ESGMYC study - Tunesi, Simone; Dû, Damien Le; Gualano, Gina; Millet, Joan-Pau; Skrahin, Aliaksandr; Bothamley, Graham; Casas, Xavier; Goletti, Delia; Lange, Christoph; Musso, Maria; Palmieri, Fabrizio; Pourcher, Valérie; et al. (The Journal of infection, 2022)
ObjectivesLimited evidence is available on the co-administration of treatment for hepatitis C virus (HCV) and multidrug-resistant tuberculosis (MDR-TB). The objective of this study is to assess safety and effectiveness of concomitant treatment of chronic HCV-infection and MDR-TB.MethodsWe performed a retrospective, multicentre observational cohort study of patients treated concomitantly for multidrug-resistant tuberculosis and HCV-infection between January 2015 and February 2021.ResultsOverall, 23 patients were enrolled across six centres in four countries. Predominant HCV genotype was 3 (40%) and most patients had absent or mild liver fibrosis. All patients completed HCV treatment without interruptions and achieved undetectable plasmatic HCV-RNA from week 12. Sustained virological response was equally obtained for all patients with available results. Among 11 patients who had finished MDR-TB treatment at data censoring, 10 achieved cure and one died. Overall, 18 liver-related adverse events were reported in 48% of patients, the majority (94%) occurring during MDR-TB treatment but before HCV treatment was started. No liver-related serious adverse events or Grade 4 adverse events were reported.ConclusionsConcomitant treatment of HCV and MDR-TB was well tolerated and effective. HCV treatment should be considered in MDR-TB patients to reduce treatment-related hepatotoxicity and prevent progression of HCV-mediated liver disease.